Infections with Giardia duodenalis and Entamoeba histolytica/Entamoeba dispar as Hidden and Prevalent Conditions in Periurban Communities in the State of Rio de Janeiro, Brazil - Deiviane A. Calegar; Kerla J. L. Monteiro; Andressa B. Gonçalves; Márcio N. Boia; Lauren H. Jaeger; Beatriz C. Nunes; Filipe A. Carvalho-Costa (Journal of Tropical Medicine)
This study aims to assess the prevalence, distribution, and etiological profile of intestinal parasitism in children living in periurban areas in Cachoeiras de Macacu, Rio de Janeiro, Brazil. A community-based cross-sectional survey (n = 479) was carried out. Prevalence of infection with G. duodenalis and E. histolytica/E. dispar was 8.6% (n = 41) and 13.4% (n = 64), respectively. Infection with G. duodenalis was significantly more frequent among children living in poor families (24/187 (12.8%) vs. 16/272 (5.9%); prevalence ratio (PR) = 2.18; 95% confidence interval (CI) = 1.19–3.99; p=0.011). This difference was also significant for infection with any pathogenic parasite (43/187 (23%) vs. 40/272 (14/7%); PR = 1.56; 95% CI = 1.06–2.30; p=0.026). In addition, people residing in houses with more than four inhabitants showed significantly higher positivity for infections with G. duodenalis and with E. histolytica/E. dispar (22/138 (15.9%) vs. 16/311 (5.1%); PR = 3.09; 95% CI = 1.68–5.71; p<0.001 for G. duodenalis and 32/138 (23.2%) vs. 30/311 (9.6%); PR = 2.40; 95% CI = 1.52–3.79; p<0.001 for E. histolytica/E. dispar). Laboratory diagnosis of protozoan enteric infections and effective drugs for their treatment are unmet goals in the primary health care system. Therefore, giardiasis and amebiasis are neglected conditions.